2019
DOI: 10.1371/journal.pntd.0007040
|View full text |Cite
|
Sign up to set email alerts
|

Potential public health benefits from cat eradications on islands

Abstract: Cats ( Felis catus ) are reservoirs of several pathogens that affect humans, including Toxoplasma gondii . Infection of pregnant women with T . gondii can cause ocular and neurological lesions in newborns, and congenital toxoplasmosis has been associated with schizophrenia, epilepsy, movement disorders, and Alzheimer’s disease. We compared seroprevalence of T . gondii and ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 60 publications
0
18
0
Order By: Relevance
“…It is believed that cats are the main carriers and transmitters of T. gondii infection to humans [46]. Several studies have observed high IgG seropositivity related to the presence of cats [28,47]. In the present study, the seroprevalence of T. gondii among pregnant women who had cats was higher than in pregnant women who did not have cats.…”
Section: Plos Onementioning
confidence: 37%
See 1 more Smart Citation
“…It is believed that cats are the main carriers and transmitters of T. gondii infection to humans [46]. Several studies have observed high IgG seropositivity related to the presence of cats [28,47]. In the present study, the seroprevalence of T. gondii among pregnant women who had cats was higher than in pregnant women who did not have cats.…”
Section: Plos Onementioning
confidence: 37%
“…Other examples include sanitary practices and eating/drinking habits, presence of household felines, poor or lower socioeconomic status, contact with soil, lack of knowledge about the disease, and the overall climate conditions that allow for the protracted environmental survival of the parasite's oocysts. In addition, felids infected with T. gondii are largely asymptomatic and can spread the infection, contributing to high infection rates [12,28,29].…”
Section: Plos Onementioning
confidence: 99%
“…The studies cited by Wolf et al [2] confirm the risks and add the charge that allowing a cat to roam freely is '...intentional contamination of the environment with a potentially lethal zoonotic pathogen' [104]. In this context, De Wit et al [58] make the case that eradicating cats on islands is likely to have public health benefits through decreased exposure to T. gondii.…”
Section: Claim Of Misinformation Responsementioning
confidence: 99%
“…With regard to public health (and, on occasion, health of companion and agricultural animals), it is well-established that cats carry a range of species-specific and zoonotic diseases and parasites that can be a concern to public health, the health of companion animals or wildlife, and agricultural production (e.g., [55,56], [57], chapter 8). For example, in a consideration of human seroprevalence to the cat-borne parasite Toxoplasma gondii on Mexican offshore islands, the authors concluded that eradication of cat populations, not control of them, could be a public health benefit [58]. Woinarski et al ([57], chapter 8) provide an extensive review of the distribution of T. gondii in Australia, including estimates of human health costs, while Stelzer et al [59] assess costs for livestock production internationally, including Australia.…”
Section: Tnr Will Reduce Problems Associated With Urban Cat Populationsmentioning
confidence: 99%
“…The control and eradication of invasive species is a powerful conservation tool for biodiversity, particularly on islands where the eradication of invasive vertebrates has resulted in significant biodiversity benefits (Tershy et al 2012, Jones et al 2016, Brooke et al 2018), yet understanding of how this conservation tool benefits people and the sustainability of economies is limited. It is well established that biodiversity and human well-being are linked (Díaz et al 2018), including evidence that invasive vertebrates impact local economies and food security through crop damage, erosion and biodiversity losses, and some of these invasive vertebrates are also known to transmit zoonotic pathogens to island human residents (Stenseth et al 2003, Doherty et al 2016, de Wit et al 2019). An analysis of these benefits is especially relevant for small island developing states (SIDS) and other islands with developing economies, many of which host some of the most globally important, threatened biodiversity (Kier et al 2009) and isolated human populations with limited economic development opportunities (Pelling & Uitto 2001, Scheyvens & Momsen 2008.…”
Section: Introductionmentioning
confidence: 99%